2009
DOI: 10.5194/nhess-9-2119-2009
|View full text |Cite
|
Sign up to set email alerts
|

Towards a definition of a real-time forecasting network for rainfall induced shallow landslides

Abstract: Abstract. PREVIEW is an European Commission FP6 Integrated Project with the aim of developing, at an European level, innovative geo-information services for atmospheric, geophysical and man-made risks. Within this framework, the Landslides Platform Service 2 (forecasting of shallow rapid slope movements) has developed an integrated procedure for the forecasting and warning of distributed shallow landsliding to be used for civil protection purposes.The Service consists of an automated end-to-end forecasting cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 79 publications
(79 reference statements)
1
57
0
Order By: Relevance
“…An inventory map of the landslides that occurred during the event is available, together with radar recordings of the rainfall (Segoni et al, 2009).…”
Section: Valle Armeamentioning
confidence: 99%
See 2 more Smart Citations
“…An inventory map of the landslides that occurred during the event is available, together with radar recordings of the rainfall (Segoni et al, 2009).…”
Section: Valle Armeamentioning
confidence: 99%
“…In the modeling the values of the hydrological and geotechnical parameters were differentiated on a lithological basis using literature data (Segoni et al, 2009(Segoni et al, , 2012 and are reported in Table 1.…”
Section: Valle Armeamentioning
confidence: 99%
See 1 more Smart Citation
“…These maps were validated with an inventory of the shallow landslides triggered by the rainfall event used in the simulations. The inventory includes 141 shallow movements (mainly debris flows and soil slips) that damaged properties, roads and assets (in addition to causing injuries to one person) (Segoni et al 2009). As can be seen also from Fig.…”
Section: Results and Validationmentioning
confidence: 99%
“…The evolution of the slope stability is computed through 24 time steps (1 h each) making use of distributed rainfall maps (1.75 km spatial resolution) obtained by means of radar measurements and downscaling techniques (Segoni et al 2009). …”
Section: Model Applicationmentioning
confidence: 99%